Synoptic 129I and CFC–SF6 Transit Time Distribution (TTD) Sections Across the Central Arctic Ocean From the 2015 GEOTRACES Cruises - Smith, John N.; Smethie Jr., William M.; Casacuberta, Núria; id_orcid:0 000-0001-7316-1655 (Journal of Geophysical Research: Oceans, 2022)
ISSN:0148-0227 ISSN:2169-9275